HISTORY OF LATIN LANGUAGE AND TEACHING TECHNOLOGY (American Journal of Interdisciplinary Research and Development, 2024)
This article traces the evolution of Latin language education, highlighting traditional pedagogy and the integration of technology. It discusses ancient methods, medieval preservation efforts, and modern digital innovations, emphasizing the enduring relevance of Latin.